Phylotypic Profiling, Distribution of Pathogenicity Island Markers, and Antimicrobial Susceptibility of Escherichia coli Isolated from Retail Chicken Meat and Humans - Asmaa Sadat; Hazem Ramadan; Mohamed A. Elkady; Amal Mahmoud Hammad; Mohamed M. Soliman; Salama M. Aboelenin; Helal F. Al-Harthi; Amira Abugomaa; Mohamed Elbadawy; Amal Awad (MDPI AG, 2022)
Escherichia coli (E.coli) found in retail chicken meat could be causing a wide range of infections in humans and constitute a potential risk. This study aimed to evaluate 60 E. coli isolates from retail chicken meat (n = 34) and human urinary tract infections (UTIs, n = 26) for phylogenetic diversity, presence of pathogenicity island (PAI) markers, antimicrobial susceptibility phenotypes, and antimicrobial resistance genes, and to evaluate their biofilm formation capacity. In that context, confirmed E.coli isolates were subjected to phylogrouping analysis using triplex PCR, antimicrobial susceptibility testing using the Kirby-Bauer disc diffusion method; PAI distribution was investigated by using two multiplex PCRs. Most of the chicken isolates (22/34, 64.7%) were identified as commensal E. coli (A and B1), while 12 isolates (35.3%) were classified as pathogenic virulent E. coli (B2 and D). Similarly, the commensal group dominated in human isolates. Overall, 23 PAIs were detected in the chicken isolates; among them, 39.1% (9/23) were assigned to group B1, 34.8% (8/23) to group A, 4.34% (1/23) to group B2, and 21.7% (5/23) to group D. However, 25 PAIs were identified from the human isolates. PAI IV536 was the most prevalent (55.9%, 69.2%) PAI detected in both sources. In total, 37 (61.7%) isolates of the chicken and human isolates were biofilm producers. Noticeably, 100% of E. coli isolates were resistant to penicillin and rifamycin. Markedly, all E. coli isolates displayed multiple antibiotic resistance (MAR) phenotypes, and the multiple antibiotic resistance index (MARI) among E. coli isolates ranged between 0.5 and 1. Several antibiotic resistance genes (ARGs) were identified by a PCR assay; the sul2 gene was the most prevalent (38/60, 63.3%) from both sources. Interestingly, a significant positive association (r = 0.31) between biofilm production and resistance to quinolones by the qnr gene was found by the correlation analysis. These findings were suggestive of the transmission of PAI markers and antibiotic resistance genes from poultry to humans or humans to humans through the food chain. To avoid the spread of virulent and multidrug-resistant E. coli, intensive surveillance of retail chicken meat markets is required.